Summability approximation theorems of triple random variables (2022)
The purpose of this article is to extend Chow, Teicher, Savas and Patterson results to higher dimension. To obtain this we consider multidimensional totally monotonic and independent identically random variables. Using these concepts we show a series of approximation type theorems.